Development of Interactive Multimedia Based on Discovery Learning in Science Enriched with Islamic Concepts Oriented to HOTS (Higher Order Thinking Skills) - Syefrinando, Boby; Asyhar, Rayandra; Sofyan, Sofyan; Wulandari, Bunga Ayu; Daulay, Hermalina (UIN Fatmawati Sukarno Bengkulu, 2026)
The aim of this research is to determine the validity, practicality, and effectiveness of interactive multimedia based on Discovery Learning enriched with HOTS-oriented Islamic concepts for elementary school students. The development model used in this study was the PLOMP model, which consists of preliminary research, development or prototyping, and assessment phases. This study was conducted at an elementary school in Jambi City during the even semester of the 2023/2024 academic year. Data were collected using material validation instruments, instructional design validation instruments, multimedia validation instruments, Qur'anic interpretation validation instruments (Islamic studies), and student response instruments. The data analysis used descriptive statistics. The results showed that the developed multimedia falls into the “very valid” and “very practical” categories. Furthermore, the effectiveness analysis revealed a moderate gain score, indicating that the multimedia is effective in enhancing students' higher-order thinking skills. These findings suggest that the interactive multimedia developed is appropriate for use in elementary thematic learning to support 21st-century learning goals.